Preliminary criteria for the very early diagnosis of systemic sclerosis: results of a Delphi Consensus Study from EULAR Scleroderma Trials and Research Group. Issue 3 (15th November 2010) - Avouac, J; Fransen, J; Walker, UA; Riccieri, V; Smith, V; Muller, C; Miniati, I; Tarner, IH; Randone, S Bellando; Cutolo, M; Allanore, Y; Distler, O; et al.
Abstract : Objective: To identify a core set of preliminary items considered as important for the very early diagnosis of systemic sclerosis (SSc). Methods: A list of items provided by European League Against Rheumatism (EULAR) Scleroderma Trial and Research(EUSTAR) centres were subjected to a Delphi exercise among 110 experts in the field of SSc. In round 1, experts were asked to choose the items they considered as the most important for the very early diagnosis of SSc. In round 2, experts were asked to reconsider the items accepted after the first stage. In round 3, the clinical relevance of selected items and their importance as measures that would lead to an early referral process were rated using appropriateness scores. Results: Physicians from 85 EUSTAR centres participated in the study and provided an initial list of 121 items. After three Delphi rounds, the steering committee, with input from external experts, collapsed the 121 items into three domains containing seven items, developed as follows: skin domain (puffy fingers/puffy swollen digits turning into sclerodactily); vascular domain (Raynaud's phenomenon, abnormal capillaroscopy with scleroderma pattern) and laboratory domain (antinuclear, anticentromere and antitopoisomerase-I antibodies). Finally, the whole assembly of EUSTAR centres ratified with a majority vote the results in a final face-to-face meeting. Conclusion: The three Delphi rounds allowed us to identify the items considered by experts as necessary for the very early diagnosis of SSc. The validation of these items to establish diagnostic criteria is currently ongoing in a prospective observational cohort.